Non-organic Vision Loss in the Afghanistan and Iraq Conflicts. (4th July 2017) - Broderick, Kevin M.; Ableman, Thomas B.; Weber, Eric D.; Enzenauer, Robert W.; Wain, Harold J.; Wroblewski, Keith J.
ABSTRACT: Non-organic visual loss (NOVL), defined as a decrease in visual acuity or field without an identifiable organic cause, can be challenging to diagnose, especially in patients whose NOVL is superimposed on some component of true organic pathology. Exposure to combat puts soldiers at risk of emotional distress and physical trauma, which can contribute to the development of NOVL with conversion disorder or malingering. This case series describes six patients with NOVL who sustained ocular or non-ocular injuries while serving in combat operations in Iraq and Afghanistan, and highlights diagnostic pearls and components of inter-disciplinary management in the unique military context.